Spinal cord stimulation restores locomotion in a Parkinson's disease patient and rodents - Jacob C. Slack; Benjamin Rees; Eleonora Borda; Jonah Slack; Miguel A.L. Nicolelis; S. Elizabeth Zauber; Kunal Gupta; Amol P. Yadav (Brain Stimulation)
Introduction: Dorsal column stimulation (DCS) of the spinal cord is emerging as a promising new technology to treat Parkinson's disease (PD). However, optimal stimulation settings that maximize its therapeutic effect on PD symptoms are yet to be determined. To optimize DCS therapy, it is necessary to understand its impact on pathological brain oscillations and to deliver stimulation triggered by neurophysiological biomarkers of PD. Materials and methods: We developed beta-triggered DCS (BT-DCS), where DCS was triggered by ongoing corticostriatal beta oscillations, and tested it in the bilateral intra-striatal 6-hydroxydopamine (6-OHDA) rat model of PD. To evaluate the translational potential of DCS in humans, we recorded local field potentials (LFPs) from bilateral subthalamic nucleus (STN) electrodes in a sixty-year-old PD subject with freezing of gait (FOG) symptoms before and three days after implantation of DCS leads. Results: DCS triggered by corticostriatal beta oscillations facilitated a pro-locomotion brain state that improved locomotion, reduced akinesia, and desynchronized ongoing oscillations in the rat model. BT-DCS achieved higher efficacy with less overall charge delivery than continuous stimulation. In the PD subject, DCS increased gait velocity and stride length, reduced freezing episodes, and desynchronized subthalamic nucleus (STN) beta oscillations, while modulating phase-amplitude coupling (PAC). When applied simultaneously with deep brain stimulation (DBS), DCS had a combinatory effect on gait improvement. Conclusion: Based on the effective implementation of BT-DCS in modulating supraspinal pathological brain activity in rats, we envision that incorporating a brain biomarker signal in delivering DCS therapy in humans could improve relief from Parkinsonian gait issues.